PREVALENCE OF VITAMIN B12 DEFICIENCY IN TYPE 2 DIABETIC PATIENTS - BY DR. N.N.ANAND; DR. MUKKAMALA VINDHYA (International Journal of Pharma and Bio Sciences, 2014)
The prevalence of vitamin B12 deficiency has been found to be high in type 2diabetic patients who may cause peripheral neuropathy. Hence the identification of vitamin B12 deficiency is important because simple vitamin B12 replacement can improve the neurological symptoms. The aim of the present study is to assess the prevalence of vitamin B12 deficiency in patients with type 2 diabetes, who are in treatment. To evaluate the association of B12 deficiency with diabetic neuropathy.Study subjects were selected from the type 2 diabetic patients being treated in our hospital who had had an assessment for diabetic neuropathy and serum vitamin B12 levels are tested.Vitamin B12 deficiency was seen in 11.5% of subjects, 70% of which were on vitamin supplementation.62.4% had diabetic neuropathy. Among the patients receiving vitamin supplementation majority (65.4%) had mild to moderate neuropathy. The study concluded that 1.Prevalence of B12 deficiency is relatively low among type 2 diabetic patients undergoing treatment.2.Mild and moderate form of neuropathy was more common probably due to vitamin supplementation that prevented further progression.3.Therefore early detection of vitamin B12 deficiency in prediabetic stages would be useful for prevention of neurological disorders by vitamin supplementation.